ENTROPY APPROACH FOR VOLATILITY OF WIND ENERGY - Calik, Sinan; Metin Karakas, Ayse (Vinca Inst Nuclear Sci, 2019)
In this study, we give the practice of entropy in wind energy. Firstly, we fit marginal distributions to each of the variables and later demonstrate the notion of entropy to perform a comparison the wind energy data of the stations (Bursa, Elazig, Istanbul, Mugla, Rize, Tokat, Van, and Zonguldak) that have been examined in a period 2015-2018. The results of probability distribution fitting to these wind energy variables show that the wind energy time series of Bursa, Elazig, Istanbul, Mugla, Rize, Tokat, Van, and Zonguldak are best resubmitted by Gamma Burr and Lognormal distributions. Later, we calculate Shannon entropy for several various values, Tsallis entropy, Renyi entropy, and the approximate entropy. We form calculation outcomes with these entropies for daily data.
Keywords: Shannon entropy; Tsallis entropy; approximate entropy; wind energy; Renyi entropy